Participatory budgeting as a tool of environmental improvements in Polish cities - Arnold Bernaciak; Agnieszka Rzeńca; Agnieszka Sobol (Economic and Environmental Studies (E&ES), 2017)
The phenomenon of participatory budgeting in Polish cities shows growing awareness of citizens' role in local development. Participatory budgeting is a tool of partial empowerment of residents through local budgetary policy. A social energy released by initiatives and proposed projects allows for implementation of relevant activities that from the residents' perspective improve quality and comfort of urban life. Research problem around which the article is focused is a question to what extent an interest of inhabitants is related to projects and tasks of environmental character in their cities. The empirical part of the paper presents an analysis of participatory budgeting in Katowice, ód̈Y and Pozna\~n and applies to projects reported in 2015 and realized in 2016. The aim of this article is to identify the activities of residents of the selected cities related to improvement of the quality of environment through participatory budgeting. The studies clearly show that despite the apparent differences between the cities, the participatory budgeting is an important area of creativity and innovation of the residents towards quality of urban environment.
Keywords: Q58; O15; O29; 330; local development; participatory budgeting; environmental protection